Application of Magnetotellurics and Transient electromagnetic in Kibiro Geothermal Prospect-Western Uganda. - Nur, Andi Agus; Mutebi, Denis; Taufan, Yoqi Ali; ilmi, Irpan (Faculty of Geological Engineering, Universitas Padjadjaran, 2019)
ABSTRACTGeophysics is an extremely important tool in geothermal exploration. Magnetotellurics (MT) and Transient electromagnetic (TEM) techniques are some of the widely used geophysical exploration techniques in Kibiro Geothermal prospect in Western Uganda. Between 2004 and 2016, a total of 157 TEM and 64 MT stations were acquired using DGSM Geonics Protem 57, Phoenix, and Zonge GDP32-12 systems. A central loop system receiver for TEM survey was used and frequency range for MT survey was between 0.5 and >200 Hz. The MT and TEM surveys imaged low resistivity clay-rich lake beds that cap a higher resistivity and potentially permeable clastic reservoir below 150 m depth. The unusually very low resistivity zone on top of the clay rich sediments inferred a hydrothermally altered sedimentary clay zone; and therefore a hot permeable aquifer exists below 150km depth. MT data imply that the North Tooro-Bunyoro (NTB) Fault dips steeply beneath sediments to the northwest.Key words: Geophysics, Magnetotellurics, Electromagnetics, resistivity, Clay.